1992
DOI: 10.1021/ja00041a038
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the ionizable metal cluster-electrode surface analogy: infrared spectroelectrochemistry of [Pt24(CO)30]N, [Pt26(CO)32]N, and [Pt38(CO)44]N (n = 0 to -10) and comparisons with potential-dependent spectra of carbon monoxide adlayers on platinum surfaces

Abstract: Infrared spectroelectrochemistry has been utilized to explore the vibrational properties of the high-nuclearity platinum carbonyl clusters [PtM(CO)3o]", [Pt26(CO)32]", and [Pt38(CO)44]" as a function of the charge n in dichloromethane, acetonitrile, acetone, tetrahydrofuran, and methanol. The clusters exhibit unusually reversible voltammetric and spectroelectrochemical behavior, with a sequence of redox steps spanning = 0 to (in one case) -10, having formal potentials, E¡, between ca. 0.5 and -2.5 V vs ferroce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
131
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 1 publication
8
131
0
Order By: Relevance
“…[24] As expected, the n( 12 CO) bands are shifted on isotopic 13 CO substitution by 44 cm À1 (Figure 6b). Although less intense and less well defined, it is apparent that the n(CN) bands are also shifted (by about 20 cm À1 ) upon 13 CO substitution.…”
supporting
confidence: 80%
“…[24] As expected, the n( 12 CO) bands are shifted on isotopic 13 CO substitution by 44 cm À1 (Figure 6b). Although less intense and less well defined, it is apparent that the n(CN) bands are also shifted (by about 20 cm À1 ) upon 13 CO substitution.…”
supporting
confidence: 80%
“…as protective ligands. [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143] Furthermore, previous studies have demonstrated that size-controlled metal NCs can be loaded on a support by adsorbing such precise metal NCs on the support and then removing the protective ligands by calcination ( Figure 3C). [144][145][146]…”
Section: Control Of Cocatalystsmentioning
confidence: 99%
“…[12][13][14][15][16][17] For example [W 6 CCl 18 ] n-(n = 0 to 4), 18 [W 6 NCl 18 ] n-(n = 1 to 3), 19 [FeS 8 (PEt 3 ) 6 ] n+ (n = 0 to 4) 20 and [Mo 6 S 8 (PEt 3 ) 6 ] n (n = 1+ to 2-) 21 have been described; while the hexanuclear cluster compounds with edge bridged halide ligands also exhibit extensive redox behaviour, 22-24 and redox pairs such as [Ta 6 Cl 14 (PEt 3 ) 4 ] n+ (n = 0, 1) have been isolated. 25 Up to ten sequential reversible reductions have been reported for the high-nuclearity platinum cluster [Pt 26 (CO) 32 ] n (n = 0 to -10). 26 EPR measurements have also been reported for a variety of medium and high-nuclearity clusters.…”
Section: Introductionmentioning
confidence: 99%
“…25 Up to ten sequential reversible reductions have been reported for the high-nuclearity platinum cluster [Pt 26 (CO) 32 ] n (n = 0 to -10). 26 EPR measurements have also been reported for a variety of medium and high-nuclearity clusters. [27][28][29][30][31][32][33] In the mono-metallic hydride arena, EPR studies on the redox pairs of 15 and 17-electron mono-nuclear hydrido 2+ .…”
Section: Introductionmentioning
confidence: 99%